LAS FUENTES DEL CRECIMIENTO DE LA POBLACION AGRICOLA ENLA PARTE CENTRAL DE EL BAJIO 19541974 - MARTIN DEL CAMPO, ANTONIO; EGUEZ SOLIS, JOSE (Centro de Economía Agrícola, Colegio de Posgraduados, 1978)
si
AGRO
Keywords: FUENTES, CRECIMIENTO, POBLACION AGRICOLA, CENTRAL DE EL BAJIO, 1954, 1974; CIENCIAS AGRARIAS; AGRONOMIA; POBLACION AGRICOLA